2014
DOI: 10.1177/1938640014532129
|View full text |Cite
|
Sign up to set email alerts
|

A Single Platelet-Rich Plasma Injection for Chronic Midsubstance Achilles Tendinopathy

Abstract: Therapeutic, Level IV: Retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
0
25
1
2
Order By: Relevance
“…The follow-up in those studies lasted 24 weeks and 28 months respectively. As for Achilles tendinopathy, several other studies also demonstrated a decrease in pain following a PRP injection [15][16][17]. To the authors' opinion, the lack of significant results in the tendon-specific part of the present study is therefore due to the small number of patients recruited.…”
Section: Are There Biologic Factors Of Good Prognosis After a Platelecontrasting
confidence: 52%
“…The follow-up in those studies lasted 24 weeks and 28 months respectively. As for Achilles tendinopathy, several other studies also demonstrated a decrease in pain following a PRP injection [15][16][17]. To the authors' opinion, the lack of significant results in the tendon-specific part of the present study is therefore due to the small number of patients recruited.…”
Section: Are There Biologic Factors Of Good Prognosis After a Platelecontrasting
confidence: 52%
“…However, the evidence for use in human chronic Achilles tendinopathy remains insufficient [60,50,74,56]. In humans, the use of PRP for Achilles tendinopathy is no more beneficial than the use of placebo treatment or control [67,16,62] Several studies suggesting an improvement of clinical symptoms provide weak evidence with a lack of control groups [20,23,49,51].…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…Over eight clinical human trials, the vast majority of patients suffering from chronic, recalcitrant tendinosis saw significant and substantial reductions in pain [88][89][90][91][92][93][94][95] and increases in joint function [72,88,90,[92][93][94][95] when treated with PRP without supplemental procedures. These patients had experienced symptoms of tendonosis for at least 3 months and had not responded to nonsurgical interventions [88][89][90][92][93][94][95].…”
Section: Prp For Chronic Tendinopathiesmentioning
confidence: 99%
“…Nine of ten patients who had been forced to leave their jobs due to their injuries were able to return to work, and 18 of 22 treated athletes were able to resume playing their sports. In a similar study, 32 patients suffering from midsubstance Achilles tendinosis were treated with a single PRP injection [91]. Within 6 months, 25 patients were asymptomatic.…”
Section: Prp For Chronic Tendinopathiesmentioning
confidence: 99%